Translation shifts of pronoun in bilingual novel twilight - Ni Made Verayanti Utami; Putu Desi Anggerina Hikmaharyanti (Politeknik Negeri Bali, 2019)
Translation could be defined as converting one language (Source Language) to another language (Target Language) so that the target language could convey the intended message in the source language. In translation, a shift is something unavoidable. Catford (1965) said that shift is departures from formal correspondence in the process of going from the SL to the TL. Translation can be done in many kinds of text, including literary. So the shift may also happen in many kinds of literary, in this paper it is focused on novel. Considering the shift happened in various kinds of literary, this study entitled Translation Shifts of Pronoun in Bilingual Novel Twilight attempts (1) classify the types of translation shift of pronoun, (2) examine the translation techniques, and (3) investigate the factors lead the application of particular translating technique done by the translator in the translation of Twilight in English version to Twilight in Indonesian version. The data focus on the translation of pronouns found in the bilingual novel of Twilight. From the data found, there are translation shift in different types which belongs to the theory proposed by Catford (1965). The method of collecting the data in this research is a direct observation method. The bilingual novel of Twilight was read. Then, the pronouns that represent the translation shift were chosen. After the data collected, they were analyzed. The data analyzed was the results of the research. There are two main theories used in analyzing the data, those are the theory of translation shift is proposed by Catford (1965) and the theory of translation technique is proposed by Molina ad Albir (2002) and supporting theory from Nida (2000) about factors lead the application of particular translating technique done by the translator. In the end, it is found that there are two types of shift which are unavoidable in translation found. They are shifts in grammatical categories or transposition and shift of point of view or modulation. There are six out of eight-teen kinds of translation techniques used in this study. Also, the factors leading to the application of the particular technique of translation in this study are linguistic factors, cultural factors, and the translator’s preference.